2010
DOI: 10.3324/haematol.2010.030494
|View full text |Cite
|
Sign up to set email alerts
|

Extensive pleural and pericardial effusion in chronic myeloid leukemia during treatment with dasatinib at 100 mg or 50 mg daily

Abstract: Dasatinib is considered an effective drug in imatinib-resistant chronic myeloid leukemia. Although reported to be well-tolerated, severe events such as pleural or pericardial effusion have been reported at 140 mg daily. We examined our chronic myeloid leukemia patients treated with dasatinib at 100 mg or 50 mg daily and identified 4 of 13 patients who developed marked effusion formation. In 2 patients, grade III/IV pleural and/or pericardial effusions were recorded. All 4 patients had received previous anti-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 23 publications
0
45
1
3
Order By: Relevance
“…In cases with elevated liver enzymes, those returned to normal after the dose reduction. In cases with pleural effusion or pericardial effusion, those are resolved with supportive care and diuretics treatment after the drug discontinuation [1,12]. Diarrhea, peripheral edema or headache [1] and immunosuppression-induced vulnerability to infection was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with elevated liver enzymes, those returned to normal after the dose reduction. In cases with pleural effusion or pericardial effusion, those are resolved with supportive care and diuretics treatment after the drug discontinuation [1,12]. Diarrhea, peripheral edema or headache [1] and immunosuppression-induced vulnerability to infection was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the paper about pleural and pericardial effusion in chronic myeloid leukemia during lowdose dasatinib treatment by Krauth et al 1 They reported 4 patients who developed effusions with 50 or 100 mg daily dasatinib out of a total number of 13 patients. Pleural and pericardial effusions were grade III/IV in 2 of the patients.…”
mentioning
confidence: 98%
“…For dasatinib-treated patients, the occurrence of pleural effusion is a clinical challenge, [8][9][10][11][12] especially when pleural effusion is recurrent or accompanied by a perciardial effusion, pulmonary hypertension, or an infection. Several other non-hematologic adverse events have also been described for dasatinib, including diarrhea, skin rash, bleeding, viral re-activation, and sometimes also opportunistic infections which have been reported in patients receiving dasatinib at a dose of 2¥70 mg daily (Table 1).…”
Section: The Unique Adverse Event Profile Of Nilotinib and Dasatinibmentioning
confidence: 99%
“…9 However, even in patients receiving 100 mg once daily, pleural effusions develop and may accumulate over time. 12,13 Nilotinib-treated patients may develop increases in pancreatic enzymes, bilirubin, and fasting glucose level (Table 1). 5,14,15 Other non-hematologic adverse events include diarrhea, a folliculitis-like skin rash, and bleeding.…”
Section: The Unique Adverse Event Profile Of Nilotinib and Dasatinibmentioning
confidence: 99%